Artificial Intelligence in Machine Learning Techniques for Clustering and Classification - Angelin Rosy, M; Chaya, M (International Journal of Computer Sciences and Engineering, 2025)
Data mining is the search for hidden relationships in data set. Machine learning is implementing some of artificial learning. Machine learning is the ability to alter an existing model based on new information .Machine learning is mainly used for business learning to identify the information. The paper evaluates the performance of clustering and classification.Clustering analysis is one of the main analytical methods in machine learning. Machine learninmg is one of the leading fields where clustering is one of the significant task. Classification methods to improve business opportunity and to improve the quality os services. The machine learning in the computer system use to effectively perform a specific task without using explicit instruction.